Work-in-Progress--Specific Heat of Water Experiment: Augmented Reality Chemistry Lab - Wirjadi, Ryan; Vuong, Alex; Liu, Frank; LiKamWa, Robert (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Augmented Reality (AR) is becoming readily more available as the number of AR capable smartphones and tablets increase in popularity. With its exponential development, augmented reality offers an oppurtunity to facilitate education in online chemistry. In hopes of furthering the advancement of augmented reality in online chemistry education, we developed a boiling water experiment to show the effects of heat capacity and to create an interactive lab experiment for online learning. Our work-in-progress paper explores how the utilization of augmented reality can improve the learning process and better exhibit chemistry lab concepts.